On calculation of Laplace’s operator eigenvalues - Sapagovienė, D. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Д. И. Сапаговене. О вычислении собственных значений оператора Лапласа D. Sapagovienė. Laplaso operatoriaus nuosavų reikšmių skaičiavimo klausimu